Prevention of neutropenia as an important factor in successful chemotherapy for head and neck cancer - L. G. Babicheva; S. O. Podvyaznikov (Опухоли головы и шеи)
Despite the advances in supportive care for cancer patients, they often develop such a serious complication of chemotherapy as febrile neutropenia. This disorder is the main cause of reduced treatment efficacy because of the lower doses of cytostatics or even withdrawal of myelosuppressive therapy in some cases. The mortality rate from infectious complications of febrile neutropenia currently reaches 10 %.Presence of risk factors in combination with aggressive chemotherapy necessitates prevention of febrile neutropenia to reduce potential risks of complications. Synthetic granulocyte colony-stimulating factors can be used to address this issue.Among patients with head and neck tumors, the most vulnerable population includes individuals receiving TPF or DCF regimen or chemoradiotherapy. Such patients require preventive administration of granulocyte colony-stimulating factors. Patients with grade III–IV neutropenia require prevention of febrile neutropenia with pegylated forms of granulocyte colony-stimulating factors (such as empegfilgrastim). This will ensure optimal treatment outcomes.